GIS-material for the archaeological project: Lundby Backgård - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
A archaeological assessment (phase 2) was performed by the Swedish National Heritage Board's Contract Archaeology Service, UV Öst, at Lundby Backgård in Mjölby, due to a local plan containing 40 new building plots. During the evaluation survey, carried out in June 2003, an area with hearths and wall trenches was discovered. The same kind of features, dated to the Neolithic, have been found only a few kilometres from the survey area. The features were excavated during the evaluation, seeing that the area containing archaeological remains was very limited.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the archaeological assessment was to determine whether any archaeological remains were going to be affected by the development plans in the area, and if so, to what extent.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
En arkeologisk utredning, etapp 2 utfördes av Riksantikvarieämbetet UV Öst vid Lundby Backgård i Mjölby på grund av ett förslag till detaljplan över 40 nya villatomter. Vid utredningen i juni 2003 upptäcktes ett område med härdar och/eller väggrännor. Denna typ av anläggningar har dokumenterats bara några kilometer från det nu aktuella området och daterats till neolitisk stenålder. UV Öst bedömde i samråd med Länsstyrelsen vid undersökningstillfället att fornlämningen kunde dokumenteras och tas bort då fornlämningsområdet var av mycket begränsad art.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med den arkeologiska utredningen var att avgöra om lagskyddade fornlämningar skulle komma att beröras av exploateringsföretaget och i så fall av vilken art och till vilken utsträckning.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Lundby Backgård
Keywords: stone age; stenålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi